2020
DOI: 10.1101/2020.02.11.943860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet TSP-1 Controls Prostate Cancer-Induced Osteoclast Differentiation and Bone Marrow-Derived Cell Mobilization through TGFβ-1

Abstract: The development of distant metastasis is the main cause of prostate cancer (CaP)related death with the skeleton being the primary site of metastasis. While the progression of primary tumors and the growth of bone metastatic tumors are well described, the mechanisms controlling pre-metastatic niche formation and homing of CaP to bone remain unclear. Through prior studies, we demonstrated that platelet secretion was required for ongoing tumor growth and pre-metastatic tumor-induce bone formation and bone marrow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
12
1
1
Order By: Relevance
“…Downregulation of the TGFβ pathway may block communication between the primary tumour and bone microenvironment, and thus may block the formation of the premetastatic niche in skeleton tissues; however, this would result in no alteration in the growth of the primary tumour. It seems that the TGFβ pathway is a promising anti-metastatic molecular target and the concentration of TGFβ in platelets might represent a potential biomarker of cancer aggressiveness [ 88 ].…”
Section: Platelet Tgfβ In a Cancermentioning
confidence: 99%
“…Downregulation of the TGFβ pathway may block communication between the primary tumour and bone microenvironment, and thus may block the formation of the premetastatic niche in skeleton tissues; however, this would result in no alteration in the growth of the primary tumour. It seems that the TGFβ pathway is a promising anti-metastatic molecular target and the concentration of TGFβ in platelets might represent a potential biomarker of cancer aggressiveness [ 88 ].…”
Section: Platelet Tgfβ In a Cancermentioning
confidence: 99%
“…Our prior studies demonstrated that subcutaneous RM1 tumor growth induced bone formation and that platelets governed this pre-metastatic communication with the bone microenvironment ( 7 , 29 ). To examine whether deletion of bone marrow-derived SCF would alter the bone microenvironment, bone sections from tumor-bearing mice were stained for tartrate-resistant acid phosphatase (TRAP) positive osteoclasts to determine osteoclast number and measure bone histomorphometry.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of Sca-1 positive and endomucin vasculature, markers for hematopoietic stem/tumorigenic cells and blood vessels, respectively, within the bones of mice with ER+ E0771/Bone derived tumors were significantly increased when compared with TN derived tumors. Previous studies across multiple cancer types have demonstrated that tumors can modulate the premetastatic bone microenvironment to become a more hospitable environment by increasing hematopoietic stem cells and vasculature [44][45][46]. Thus, the numbers of potential colonization niches were increased in mice with ER+ E0771/Bone tumors.…”
Section: Discussionmentioning
confidence: 97%